THE ROLE OF OPENINGS AND THEIR IMPACT ON USER INTERACTION - Aanisah Ayu Wulandari; Harry Kurniawan; Ramadhan, Muhammad Afi Tegar (Built Environment Studies, 2024)
The evolution of building openings, particularly windows, has expanded beyond basic functions like light and ventilation to include energy efficiency, aesthetics, and technology integration, influencing user behavior and interactions. However, these interactions remain underexplored. This study examines how windows impact user behavior in Yogyakarta City and Sleman Regency. Using qualitative field observations at 12 locations and 22 window points, interactions were categorized into three types: openings as objects of attention without physical interaction, openings approached with physical interaction, and openings approached with unusual interactions. These categories were analyzed based on physical, spatial, and psychological aspects. The influence of each element was evaluated by comparing the similarities within interaction categories across different cases. The research identified three types of interactions: attention without interaction, physical interaction, and unusual interaction. Findings reveal that window characteristics, spatial context, and psychological perceptions collectively shape user engagement. The study emphasizes the importance of these factors in window design, offering valuable insights for creating more user-centric, interaction-oriented window designs in modern architecture.